2023
DOI: 10.3390/agriculture13101913
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Quality Properties of Pears during Storage Using Hyper Spectral Imaging System

Ebrahim Taghinezhad,
Vali Rasooli Sharabiani,
Mohammadali Shahiri
et al.

Abstract: This paper presents a comprehensive analysis of the application of visible–near-infrared (Vis/NIR) spectroscopy for the estimation of various chemical attributes of pear fruit. Specifically, the paper investigates how pH, titratable acidity (TA), soluble solids content (SSC), and Vitamin C change as the pear undergoes different storage durations and temperatures. To obtain the most accurate prediction models, we applied a variety of pre-processing techniques to the acquired spectra. Notably, the combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additionally, recent studies have also shown that HSI is feasible for visualizing the distribution of internal quality in fruits, such as SSC and PH distribution of cherries, mandarins and kiwifruit [12][13][14], and firmness of peach [15]. Beyond these examples, research using hyperspectral imaging and chemometrics has shown promising results in maturity analysis and quality evaluation of blueberries, persimmons, bananas, and other fruits [16][17][18][19]. The above researches mainly focus on the prediction of single indicators of SSC and hardness during the sample maturity stages.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies have also shown that HSI is feasible for visualizing the distribution of internal quality in fruits, such as SSC and PH distribution of cherries, mandarins and kiwifruit [12][13][14], and firmness of peach [15]. Beyond these examples, research using hyperspectral imaging and chemometrics has shown promising results in maturity analysis and quality evaluation of blueberries, persimmons, bananas, and other fruits [16][17][18][19]. The above researches mainly focus on the prediction of single indicators of SSC and hardness during the sample maturity stages.…”
Section: Introductionmentioning
confidence: 99%